INTERNET FAMOUS - Stone, Danika (Swoon Reads, 2017)
Internet sensation Madison Nakama has it all! Her pop-culture rewatch site has a massive following, and fans across the world wait on her every post and tweet. And now Laurent, a fellow geek (and unfairly HOT French exchange student!), has started flirting with her in the comments section of her blog. But Laurent’s not the only one watching for Madi’s replies…Internet fame has a price, and their online romance sparks the unwanted attention of a troll. When Madi’s “real life” hits a rough patch, she feels her whole world crumbling. With Laurent’s support, can Madi rally her friends across the globe to beat the troll, or will he succeed in driving her away from everything―and everyone―she loves?